Speaking materials based on active learning activities and revised Bloom’s taxonomy: development, validation, and revision - Rampeng; Haryanto Atmowardoyo; Nurdin Noni (Center for Humanities and Innovation Studies, 2021)
As an international language, English becomes vital to master. In English, speaking is considered more crucial compared to listening, writing, and reading. Nevertheless, it is not an easy task to achieve. One solution which can ease learning speaking is presenting excellent learning materials for students. Thus, teachers are obliged to write and develop learning materials that are relevant, effective, and suitable for their students. This study aimed to give a clear overview of how to develop, validate, and revise Speaking learning materials according to active learning activities and Six steps in revised Bloom’s Taxonomy. This study was objected to offering a novelty as there was little discussion on developing learning materials, particularly speaking, based on active learning activities and revised Bloom’s taxonomy. This thus widens discussion in the field. The method used was Research & Development. The study suggested that learning material development required several steps, including six steps of Bloom’s taxonomy. The validation proposed the aspects of materials, the aspects of activities, the aspects of media, and the presentation aspects. The last, revision must be taken once the developed materials are found less suitable for learners.